The Use of Star Anise-Cinnamon Essential Oil as an Alternative Antibiotic in Prevention of Salmonella Infections in Yellow Chickens - Changcheng Li; Ziheng Xu; Wenyan Chen; Chenyu Zhou; Can Wang; Min Wang; Jingzhen Liang; Ping Wei (MDPI AG, 2022)
Salmonella is capable of harming human and animal health, and its multidrug resistance (MDR) has always been a public health problem. In addition, antibiotic-free or antibiotic-reduced policies have been implemented in poultry production. Therefore, the search for antibiotic alternatives is more urgent than ever before. The aim of this study was to assess the antibacterial activity of star anise-cinnamon essential oil (SCEO) in vitro and its prophylactic effect against the infections of Salmonella pullorum, Salmonella give, and Salmonella kentucky in vivo. The results demonstrated that SCEO is effective against Salmonella pullorum, Salmonella give, and Salmonella kentucky in vitro. Supplementation with SCEO could significantly decrease the infections of Salmonella pullorum and Salmonella give, whereas it could slightly but not significantly decrease the infection of Salmonella kentucky, while also significantly alleviating the body weight (BW) loss caused by the infections of Salmonella pullorum, Salmonella give, and Salmonella kentucky in Yellow chickens. The SCEO had the best prophylactic effect against the infection of Salmonella give in Yellow chickens, followed by the infection of Salmonella pullorum and the infection of Salmonella kentucky. The SCEO, used as an antibiotic alternative, could be an effective prevention strategy against the infections of Salmonella pullorum, Salmonella give, and Salmonella kentucky in Yellow chickens.